THE EFFECT OF SOURSOP LEAF TEA ON REDUCING BLOOD SUGAR LEVELS IN DIABETES MELLITUS PATIENTS - Rustanti, Elly; Naben, Faustina; Sari, Gevi Melliya; Setiawan, Roni (Library Unit collaborates with the Institute for Research and Community Service, College of Health Sciences Husada Jombang, 2024)
Background: In Indonesia, many people do not pay attention to healthy lifestyles in order to maintain stable blood sugar to prevent diabetes mellitus, which increases every year. Objective: The aim of this research was to determine the effect of soursop leaf tea on reducing blood sugar levels in diabetes mellitus sufferers at the Dukuh Klopo Community Health Center, Peterongan, Jombang. Method: The research design was a pre-experimental - one group pre test-post test design. The population in this study was 153 people, all sufferers of diabetes mellitus at the Dukuh Klopo Community Health Center using purposive sampling technique, a sample of 23 people. The independent variable is soursop leaf tea. The dependent variable is a decrease in blood sugar levels in diabetes mellitus sufferers. Data collection uses SOP and observation sheets with the Wilcoxon statistical test. Results: Based on the research results, it was discovered that all 23 respondents (100%) had high blood sugar levels before being given soursop leaf tea therapy. Meanwhile, after being given therapy, some respondents, namely 12 respondents (52%) were in the moderate category and 11 respondents (48%) were in the normal category. The results of the Wilcoxon test at a significance level of α = 0.05 showed that ρ<α or 0.000 < 0.05, so H1 was accepted and H0 was rejected, which means that there is an effect of soursop leaf tea on reducing blood sugar levels in diabetes mellitus sufferers at the Dukuh Klopo Community Health Center, Peterongan , Jombang. Conclusion: Giving soursop leaf tea can reduce blood sugar in diabetes mellitus sufferers and is expected to be an alternative intervention to reduce blood sugar, because soursop leaves can improve pancreatic cells by increasing their granulation. Apart from that, the high antioxidants in soursop leaves can reduce free radicals that come from hyperglycemia.